VARIABEL-VARIABEL PENENTU HOLDING PERIODS SAHAM SYARI’AH DI INDONESIA - Fitriyah, Fitriyah; Rahayu, Yayuk Sri (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2013)
This research was aimed to determine whether the variables bid-ask spread, market value, variance return and dividend payout influence holding period partially and simultaneously and to determine the variables that most influence the holding period of shares of sharia in Indonesia Stock Exchange. The population in this research are the companies listed in the Jakarta Islamic Index over the period 2007 to 2010. Sampling using a purposive sampling technique and number of sample are 10 companies.. The result shows, the variable spreads, market value, variance return, dividend payout ratio simultaneously influence the holding period. While partially, there are two variables that significantly influence the holding period that is spread and dividend payout ratio with a significant negative relationship and the spread has a significant positive relationship to the holding period at α 5%. And the most influential variable is spread. The final conclusions are on the Indonesia Stock Exchange, investors alleged psychological factor is the factor most be taken into consideration in decisions about withholding or release of a common stock.   Keyword: Holding periods, bid ask spread, market value, and variance return   Abstraksi Penelitian ini bertujuan untuk mengetahui apakah variabel bid-ask spread, market value, varians return dan dividen pay out ratio mempengaruhi holding periods secara parsial dan simultan dan untuk mengetahui variabel yang paling mempengaruhi holding period saham syariah di Bursa Efek Indonesia. Populasi dalam penelitian ini adalah perusahaan yang terdaftar di Jakarta Islamic Index selama periode 2007 sampai 2010. Sampling sebanyak 10 perusahaan ditentukan dengan  teknik purposive sampling. Hasil analisis  menunjukkan variabel bid-ask spread, market value, varians return dan dividen pay out ratio secara simultan mempengaruhi holding periods. Sedangkan secara parsial, ada dua variabel yang berpengaruh signifikan terhadap holding period yaitu dividen pay out ratio yang signifikan negatif dan bid-ask spread  signifikan terhadap holding period pada α 5%. Dan variabel yang paling berpengaruh adalah bid-ask spread . Kesimpulan terakhir adalah di Bursa Efek Indonesia, diduga faktor psikologis investor merupakan faktor yang paling dipertimbangkan dalam keputusan tentang pemotongan atau pelepasan saham biasa.   Kata Kunci: Holding periods, bid ask spread, market value, dan variance return